Mechanical Behaviour of Fenestrations in Current Aortic Endografts. (December 2021) - Jayet, Jérémie; Heim, Frédéric; Canonge, Jennifer; Coggia, Marc; Chakfé, Nabil; Coscas, Raphaël
Abstract : Objective: The aim of this study was to assess the mechanical characteristics of current commercially available fenestrated endografts (FE). The performance of the fenestrations according to the design were compared as the relationship between a bridging covered stent graft (CSG) and the fenestration. Methods: A total of 21 Zenith (Cook Medical, Bloomington, IN, USA) and 17 Anaconda (Terumo Company, Inchinnan, UK) fenestrations were studied. Radial extension tests were performed, inserting two half cylinders spaced up to 2 mm in a 7 mm diameter fenestration from each device. Branch pull out force was measured to test the stability of the assembly with a calibrated 8 mm branch and two CSGs: Advanta V12 (Atrium Medical; Hudson, NH, USA) and BeGraft Peripheral Stent Graft (Bentley InnoMed GmbH, Hechingen, Germany). A branch was inserted in both the 7 mm diameter fenestrations and in a control 7 mm fenestration. Fatigue tests were performed on the devices to assess long term outcomes of the endograft. Results: Over a 2 mm vertical displacement, the resulting loading curves look similar for both devices. The force value level was 33.4 ± 6.9 N for the Cook fenestration and 54.45 ± 18 N for the Anaconda fenestration ( p  = .001). With respect to an 8 mm calibrated branch, the required extraction strength from the fenestration was statistically significantly greater with the Anaconda device (9.5 ± 4.7 N vs. 4.49 ± 0.28 N; p  = .001). The required strength to extract the V12 CSG from a control cylindered shape was statistically significantly higher than for the BeGraft CSG (6.75 ± 2.86 N vs. 1.83 ± 0.67 N; p  = .003). The surface area of the fenestration of the Cook device was increased with cycling (7 200 cycles) compared with the Anaconda device (15.5% vs. 6.5% hole surface area increase). Conclusion: The mechanical performance of the fenestration can be fine tuned by considering its design. A CSG optimising the performance of the fenestration and the CGS–fenestration interface could reduce the risk of leakage in clinical practice.